(3OhMI GdHSJGf hfRgI GdENhGf aj efGbH GdTjN SjOi Ydj GHf YHOGdQMef GdOQYjs - (3CHhYHO Gddg eMeO(B((3aJMG(B) (3Hf Ydj Hf eMeO Hf Ydj Hf CMeO Hf eMeO GdRHGOj GdMSfj,J (B1209 (3g` s
(3ChdgG (B:s
(3CeG HYO , deG ef Gddg GdcHjQ Ydi YHOg HeYQaI GdCLhGO hNOeI GdabQGA GdCWhGQ hGdONhd ai ReQI Gdhdi GdcGed s
(3BNQgG (B:s
(3hYGed ehdGc HGdQVG hGdUHQ Ydi GdHdG, Ke JQcfi heVi , hbGd gPG SHH Jhdgi Ydjg hThbi Edjg Cg` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B297s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B689 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B179 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(390 (3O(B) s
Keywords: (3GdJGQjNs